PENGGUNAAN METODE PEMBELAJARAN DALAM MELATIH BAHASA INGGRIS PADA ANAK DI TK KINDERWORLD - Noveny, Yosi; Marmawi, Marmawi; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was carried out at Kinderworld Sungai Raya Dalam Kindergarten with 6 children, 5-6 years and  one teacher.The form of this research is qualitative research and the method in this study is a case study method. The techniques used are direct communication techniques, techniques, techniques. Incredible data collection tools. The results of this study are (1) the singing method is a method that can be used by teachers to practice English so that children can express themselves through songs they hear, and can increase children's self-confidence. (2) conversational methods are very effective in training English-speaking children in Kinderworld Kindergarten. Children become brave to say sentences using English. (3) the playing method is also very effective to use in English training because playing is a very fun method for children.  Keywords:  Learning Methods, English Practice, English For Kindergarten Children